Reexamining Sadd Al-Źarī’ah in Contemporary Islamic Family Law: An Empirical Study on the Rationale for Delaying Marriage in Pringsewu Regency - Evy Septiana Rachman; Laras Shesa; Siti Zulaikha; Qois Azizah Bin Has (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Purpose – This study is motivated by the growing phenomenon of “waithood” (marriage postponement), which, from the perspective of classical Islamic law, is often viewed as potentially harmful to society. This study aims to analyze the rationale behind marriage postponement in Pringsewu Regency and reexamine the concept of Sadd al-Źarī’ah within a more dynamic social context. Methods – This study employs a qualitative approach with an empirical-sociological focus. Primary data were collected through in-depth interviews with ten women aged 25–40 who consciously delayed marriage, as well as from the Damar Institute and IWAPI Pringsewu. Secondary data were derived from relevant documents, reports, and statistics. Analysis was conducted qualitatively through data reduction, data presentation, and drawing conclusions with interpretation using the Sadd al-Źarī’ah framework Findings – Marriage postponement is influenced by economic, educational, psychological, and sociocultural factors and reflects instrumental, reflective, and normative-contextual rationality. Postponement functions as a mechanism for partner selection and a strategy to ensure the quality of long-term relationships. The findings also indicate a shift in social norms that increasingly accept marriage postponement and the strengthening of women’s agency in determining the timing of marriage. Conceptually, delay is not always a means leading to harm (mafsadat), but can function as an effort to prevent greater risks, such as divorce, domestic disharmony, and unpreparedness to fulfill family roles. Research implications – These findings encourage strengthening premarital education, empowering women through education and economic opportunities, and developing religious approaches that are more adaptive to contemporary social dynamics.